Llama Llama Gram and Grandpa [book with audioplayer] - Dewdney, Anna (Wonderbooks., 2020)
It's an exciting day for Llama Llama; he's going to visit Gram and Grandpa Llama and spend the night his first night away from home and from Mama. But he makes sure to pack everything he needs. And there are so many fun things to do with Gram and Grandpa. It's not until he gets ready for bed that he realizes that he's forgotten something important. Fuzzy Llama. Fortunately, Grandpa Llama has a wonderful solution and soon Llama Llama is having sweet dreams.